Pengaruh Firm Size Terehadap Harga Saham Pada Bank Besar Yang Terdaftar Di Bursa Efek Indonesia - Shandy Dwi Cahyono; Moh. Fahrul Akbar Putra H; Istiono Istiono (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of firm size on stock prices in major banks listed on the Indonesia Stock Exchange for the 2022–2025 period. Firm size is measured using the natural logarithm of total assets, while stock price is measured based on the annual closing price. This study employs a quantitative approach with an associative research design. The research sample consists of five major banks, namely BBCA, BBRI, BMRI, BBNI, and BBTN, comprising a total of 20 observations. The data analysis technique used is simple linear regression. The results indicate that firm size has a positive and significant effect on stock prices, as evidenced by a t-test significance value of 0.010, which is lower than 0.05. The regression coefficient value of 2,781.50 demonstrates that every increase in firm size will increase the stock price. Furthermore, the coefficient of determination (R2) value of 0.318 indicates that firm size can explain 31.8% of the variation in stock prices, while the remaining proportion is influenced by other factors outside this study. This research supports signaling theory, suggesting that company size serves as a positive signal for investors in assessing company prospects.